Tumor Suppressors p53, p63TAα, p63TAy, p73α, and p73β Use Distinct Pathways to Repress Telomerase Expression - Yao, Yuan (American Society for Biochemistry and Molecular Biology, 2012)
The promoter of the telomerase catalytic subunit (TERT) is subject to tight regulation and remains repressed in somatic cells to ensure their limited life span and to prevent tumor initiation. Here we report that the hTERT promoter is strongly repressed by p53 and the related family members p63 and p73. We found that p53-mediated repression was different in human and mouse cells and occurred through p53-dependent transcription inhibition of c-Myc or through E-box/E2F pathways, respectively. Although p63TAα-mediated repression occurred through SP1, p63TAy-mediated repression occurred through E2F signaling. Finally, p73α- and p73β-mediated repression occurred through NF-YB2. Our results show a complex multifactorial mechanism used by p53 and its family members to keep hTERT expression under tight control.